Communality and Social Status Presented by Food in A Christmas Carol by Charles Dickens - Nummila, Aliina (My University, 2025)
Food and social status are recurring topics in Charles Dickens’ works and A Christmas Carol is no exception to that. This famous Christmas novella presents food from various angles and shows how different social groups see and treat food and dining from different perspectives. In my thesis I discuss how food is presented and treated in the novella. I analyse the social aspects of eating since A Christmas Carol is filled with sharing food and eating together with the loved ones. In this thesis I also research the differences in food and eating between different social groups in the novella. I tie the story to its context in the Victorian England, since it differs from how the world is viewed today. The thesis goes through the changes in Scrooge’s attitude and thoughts towards food and the less fortunate as with the help of the Spirits he becomes kind and caring. In the end Scrooge understands the importance of food, communal dining, and helping others. The Cratchit family has a big role in Scrooge’s change since their Christmas dinner and the atmosphere in their small home is so hearth-warming and inviting.
Keywords: Dickens, food in literature, sharing food, social status, Victorian England